Theological Rigidity Against Covid-19 Vaccines Among Rural Christian Learners in Gutu, Zimbabwe - Munyaradzi Chidarikire (International Journal of Education, Teaching, and Social Sciences, 2023)
This article explores theological rigidity and misconceptions against solutions to increase COVID-19 vaccination among rural learners in Zimbabwe. This qualitative study is anchored on socio-cultural theory by Levi Vygotsky. An interpretive paradigm embedded in a case study design was used to explore the concepts. We used a purposive sampling technique to select nineteen knowledge rich rural Christians drawn from Pentecostals, African initiated Traditional Churches and Evangelicals denominations. In-depth interviews were conducted with the selected informants. Two focus group discussions (FGDs) were administered with participants drawn from each of the three denomination categories, giving a total of six FGDs. Data generated through focus group discussions were analyzed through thematic content analysis. We found that a significant number of rural learners in Zimbabwe have not been vaccinated due to a myriad of reasons. These include their rigid theological beliefs, cultural resistance and political skepticism. Consequently, the paper recommends that there is need for the Government, Church organizations and other stakeholders to collectively engage each other and find solutions to increase the uptake of COVID-19 vaccines among rural learners.